Формализация процесса согласования документов в рамках системы управления данными - Вичугова А. А. Анна Александровна; Вичугов В. Н. Владимир Николаевич; Цапко С. Г. Сергей Геннадьевич; Цапко Г. П. Геннадий Павлович (2013, 2013)
Заглавие с экрана